Optimised thermally driven molecular stability of an SCO metal complex for TEC Seebeck generation enhancement - Megat Hasnan, Megat Muhammad Ikhsan; Said, Suhana Mohd; Sabri, Mohd Faizul Mohd; Mat Hussin, Siti Amira; Abdullah, Norbani; Nik Ibrahim, Nik Muhd Jazli; Miyazaki, Yuzuru; Salleh, Faiz; Shah, Noraisyah Mohamed (Royal Society of Chemistry, 2019)
The thermoelectricity effect allows the generation of electrical potential in an electrolyte upon application of a thermal gradient. In the previous work, the spin crossover effect in metal complexes was shown to be beneficial for generating a high Seebeck coefficient due to the high entropy associated with the conformational change accompanying the spin state change. In this study, we examine the diamagnetic stability of a spin crossover material through optimisation of the ligand chain length. We show that the diamagnetic stability of the spin crossover material can enhance the thermoelectrochemical Seebeck effect through ligand optimisation of the octahedral structure. The increase of carbon chain length from C14 to C16 in the long alkyl chain of the N-donor ligand increased Seebeck generation in a Co(iii)L16 complex to 1.94-fold that of a previously studied paramagnetic Co complex, and in a Fe(iii)L16 complex to 3.43-fold that of a less diamagnetic Fe complex. We show with DSC studies of an Fe based octahedral complex that an endothermic absorption accompanies the spin crossover transition, which enhances the Seebeck coefficient of this metal complex. Thus, we can correlate the diamagnetic stabilisation with temperature. We therefore indicate a molecular design strategy for optimisation of a spin crossover metal complex. © 2019 The Royal Society of Chemistry.